Higher dietary fibre intake is associated with lower CVD mortality risk among maintenance haemodialysis patients: a multicentre prospective cohort study. Issue 10 (28th November 2021) - Lin, Zizhen; Qin, Xianhui; Yang, Yaya; Huang, Yan; Wang, Jieyu; Kong, Yaozhong; Li, Yumin; Yang, Shenglin; Lu, Yongxin; Zhao, Yanhong; Li, Youbao; Wan, Qijun; et al.
Abstract: High fibre intake is associated with reduced mortality risk in both general and chronic kidney disease populations. However, in dialysis patients, such data are limited. Therefore, the association between dietary fibre intake (DFI) and the risk of all-cause and CVD mortality was examined in this study. A total of 1044 maintenance haemodialysis (MHD) patients from eight outpatient dialysis centres in China were included in this study. Data on DFI were collected using 24-h dietary recalls for 3 d in a week and were normalised to actual dry weight. The study outcomes included all-cause and CVD mortality. Over a median of 46 months of follow-up, 354 deaths were recorded, of which 210 (59 %) were due to CVD. On assessing DFI as tertiles, the CVD mortality risk was significantly lower in patients in tertiles 2–3 (≥0·13 g/kg per d; hazard ratio (HR) 0·71; 95 % CI 0·51, 0·97) compared with those in tertile 1 (<0·13 g/kg per d). A similar but non-significant trend was found for the association between DFI (tertiles 2–3 v. tertile 1; HR 0·83; 95 % CI 0·64, 1·07) and all-cause mortality. In summary, higher DFI was associated with lower CVD mortality risk among Chinese MHD patients. This study emphasises the significance of DFI in MHD patients and provides information that is critical for the improvement of dietary guidelines for dialysis patients.